2021
DOI: 10.1186/s13741-021-00183-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between residual neuromuscular blockade (RNMB) and critical respiratory events: a prospective cohort study

Abstract: Background Inadequate neuromuscular recovery might impair pulmonary function among adult patients who undergo general anaesthesia and might thus contribute to critical respiratory events in the post-anaesthesia care unit (PACU). The pilot study aims to understand the baseline incidence of residual neuromuscular blockade (RNMB) and postoperative critical respiratory events (CREs), which are described in a modified Murphy’s criteria in the PACU. Method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Patients with adequate spontaneous recovery to train-offour ratio greater than or equal to 0.9 can be identified only with quantitative monitoring, and these patients do not require pharmacological antagonism. The body of evidence included 16 studies (10 randomized controlled trials, 3,12,[39][40][41]47,[169][170][171][172] 2 before-after design, 44,46 3 prospective cohort studies, 42,45,48 and 1 retrospective cohort study 43 ) comparing the effects of quantitative monitoring with qualitative assessment or clinical assessment on patient outcomes. Studies enrolled a median of 135 participants (range, 30 to 17,150).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with adequate spontaneous recovery to train-offour ratio greater than or equal to 0.9 can be identified only with quantitative monitoring, and these patients do not require pharmacological antagonism. The body of evidence included 16 studies (10 randomized controlled trials, 3,12,[39][40][41]47,[169][170][171][172] 2 before-after design, 44,46 3 prospective cohort studies, 42,45,48 and 1 retrospective cohort study 43 ) comparing the effects of quantitative monitoring with qualitative assessment or clinical assessment on patient outcomes. Studies enrolled a median of 135 participants (range, 30 to 17,150).…”
Section: Discussionmentioning
confidence: 99%
“…Residual Neuromuscular Blockade. A total of five randomized controlled trials 3,12,[39][40][41] and three observational studies [42][43][44] reported lower incidences of residual neuromuscular blockade with quantitative monitoring compared with qualitative assessment or clinical assessment (supplemental tables S8 and S9, http://links.lww.com/ALN/C928). Although both train-of-four ratio thresholds and place (operating room or PACU) where residual neuromuscular blockade were assessed differently across the studies, there is general consistency in the estimated risk ratios.…”
Section: Clinical Assessment or Qualitative Assessment Versus Quantit...mentioning
confidence: 99%
See 3 more Smart Citations